Acute coronary syndromes in the very elderly: Short term prognostic performance of the SYNTAX score - Faroux, Laurent; Tassan-Mangina, Sophie; Herce, Benoit; Nazeyrollas, Pierre; Bauley, Karine; Metz, Damien (International journal of cardiology, 2017)
Acute coronary syndromes (ACS) frequently occur in elderly subjects. The high mortality associated with ACS in this population justifies the identification of factors related to poor prognosis. We aimed to evaluate the short-term prognostic performance of the SYNTAX score in a population of patients aged 85years or more presenting ACS and undergoing coronary angiography. Secondary objectives were to identify factors related to length of stay and potential markers of in-hospital death. We performed a retrospective, single-centre prognostic study including patients aged 85years or more who underwent coronary angiography for ACS over a 4year period. The primary endpoint was length of stay, and the secondary endpoint was in-hospital mortality. In total, 70 patients were included (37 men), average age 87.0±2.5years. Average SYNTAX score was 19.0±14.9. Average length of stay was 13.1±7.8days. By multivariate analysis, SYNTAX score was correlated with length of stay (p=0.008). Seven (10%) patients died in-hospital. Patients who died had a higher SYNTAX score (p=0.013) (threshold value of 25) and a lower left ventricular ejection fraction (p=0.001). They more frequently had signs of heart failure at admission (p=0.002), ST segment elevation ACS (p=0.046) and left main stem involvement (p=0.041) than survivors. In our study, SYNTAX score was associated with length of stay and in-hospital mortality. A SYNTAX score of 25 or more seems to be an indicator of poor short-term prognosis in very elderly patients with ACS.